Tailoring metal sites of FeCo-MOF nanozymes for significantly enhanced peroxidase-like activity. Issue 8 (17th March 2023) - Cheng, Xiqing; Xie, Yameng; Li, Guang; Zheng, Zhiping; Kuang, Qin
Abstract : A mixed metal–organic framework (FeCo-MOF-H2 ) with excellent peroxidase-like catalytic activity was successfully prepared, which showed great application potential in the detection of H2 O2  and glutathione. Abstract : As a type of novel artificial enzyme, metal–organic frameworks (MOFs) have attracted great research interest due to their unique inorganic–organic hybrid structure, which can be designed to exhibit different enzyme mimicking activities via finely tuning metal nodes and coordination environments. In this work, a mixed metal–organic framework (FeCo-MOF-H2 ) with excellent peroxidase-like catalytic activity was successfully prepared via low-temperature heat treatment in Ar/H2 on Co-doped Fe-based MOFs. Based on the results of a variety of spectroscopic characterization processes, it was found that the electronic structure, chemical state and coordination environment of Fe sites in Fe-based MOFs were modulated by Co doping and low-temperature heat treatment, which synergistically contribute to selective H2 O2 adsorption (HOOHad ), catalysis and fast electron transfer at those accessible metal sites for producing hydroxyl radicals (˙OH). Strikingly, in situ attenuated total reflection Fourier transform infrared (ATR-FTIR) spectrometry and steady-state kinetic studies showed that FeCo-MOF-H2 has higher affinity to H2 O2 (a smaller K m value of 0.06 mM) even when compared with natural HRP as well as reported Fe-based and Co-based nanozymes. The catalytic activity of FeCo-MOF-H2 was about 10.6 and 2.9 times compared to the pristine Co-MOF and Fe-MOF, respectively. Owing to their excellent peroxidase-like catalytic activity, the FeCo-MOF-H2 nanozymes showed great application potential in the detection of H2 O2 and glutathione, and the limit of detection and linear range are superior to those of most of the Fe-based and Co-based nanozymes reported so far. Our work provides a meaningful guidance for gaining insight into the structure–activity relationship of multivariate MOF-based nanozymes.